Evaluation of an information literacy intervention of nursing students at four Universities of Technology in South Africa - Borephe, Sello (Library and Information Studies Centre (LISC), 2014)
The delivery of high quality patient care and the preparation for lifelong learning requires that nursing students be afforded the opportunity to develop their information literacy (IL) skills. This study explored the IL skills offered to nursing students by the Universities of Technology (UoT) in South Africa. The objective of the study was to assess the effectiveness of an IL intervention for nursing students at four UoT. In South Africa, IL is recognised in higher education as one of the critical outcomes of a qualification. It covers the lifelong competencies of finding, locating, and using information to find solutions to daily problems, to enhance decision-making and to improve the creation of knowledge. The history of IL within academic libraries indicates its evolution from bibliographic instruction, user education and now IL. Most academic libraries in South Africa have placed it high in their strategic plans. In South Africa there is little information on the evaluation of IL interventions for nurses. This study endeavours to investigate the effectiveness of IL intervention for nursing students undertaken by UoT in South Africa. It moves away from subjective evaluation methods in order to establish the extent to which nursing students have benefited from the intervention. The evaluation is learner-centred, and will inform the librarians concerned about the effectiveness of IL intervention. The American College and Research Libraries (ACRL) Information Literacy Competency Standards for Higher Education were used to evaluate IL intervention at the four UoT that offer Nursing. These UoT are: Vaal University of Technology (VUT), Tshwane University of Technology (TUT), Durban University of Technology (DUT) and Cape Peninsula University of Technology (CPUT). The study used a questionnaire to assess students’ IL after their training sessions. The findings suggest that the IL interventions were effective, but that attention should be paid to their integration into curriculum. The study provided an insight into how IL interventions should be improved and offered within UoT. It recommends that IL interventions should be credit-bearing.